Formal Project Management Adoption Readiness of Emerging Contractor Firms in The Mangaung Metropolitan Municipality in The Free State of South Africa - Dr Francis Okyere,; Akaba Julius ,; Dr Agbobli Edem, (IJRDO - Journal of Business Management, 2019)
While the South African government has harnessed Emerging Contractor Firms (ECFs) as vehicles for promoting economic transformation and redressing historical economic disadvantage among previously disadvantaged groups, the capacity of these firms to transform the construction industry has been hampered by their lack of project management (PM) skills and techniques. The drive towards empowering ECFs in this industry, therefore, has been marred by evidence of poor quality construction, delays in project execution and completion leading to cost overruns and general public frustrations. Since these challenges are attributed to poor project management practices and dearth of project management skills by most ECFs, there is scope to examine the formal project management adoption readiness of ECFs. Mindful of the ECFs’ involvement in construction programmes and projects on behalf of government, this theoretical study explores the extent and significance of project management readiness of emerging contractors (ECs) in the adoption and implementation of construction projects. The thesis of this paper is that since organisational culture, organisational structure and PM skills constitute the foundation for successful project management; any effective model on project management readiness of ECFs should strongly dovetail with these organisational variables as well as an appropriate business strategy. The study recommends a holistic approach to effective project management that rides on exploitation of business strategy and these organisational variables.